2021
DOI: 10.1109/lcsys.2020.3047737
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Control of Soft Robots Based on an Enhanced 3D Augmented Rigid Robot Matching

Abstract: Despite having proven successful in generating precise motions under dynamic conditions in highly deformable soft-bodied robots, model based techniques are also prone to robustness issues connected to the intrinsic uncertain nature of the dynamics of these systems. This letter aims at tackling this challenge, by extending the augmented rigid robot formulation to a stable representation of three dimensional motions of soft robots, under Piecewise Constant Curvature hypothesis. In turn, the equivalence between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…It is noted that for α = 1, eq. ( 37) reduces to the conventional linear sliding surface ėq = −Λe q used in [17], [21]. By direct integration of eq.…”
Section: A Adaptive Control: Curvature Spacementioning
confidence: 99%
See 3 more Smart Citations
“…It is noted that for α = 1, eq. ( 37) reduces to the conventional linear sliding surface ėq = −Λe q used in [17], [21]. By direct integration of eq.…”
Section: A Adaptive Control: Curvature Spacementioning
confidence: 99%
“…Remark 3. Compared to adaptive controller in [17], the control law presented here has an additional term bsign(s), which, as shown in the stability proof, can reject the bounded input disturbances. Moreover, thanks to the adaptation law in eq.…”
Section: A Adaptive Control: Curvature Spacementioning
confidence: 99%
See 2 more Smart Citations
“…However, research has shown that classical high-gain controllers can increase the closed-loop stiffness of the system, potentially reducing the benefits of soft manipulators [7]. As a result, recent approaches have been combining feedback actions that employ low gains with feed-forward actions [8] or with adaptive algorithms [9]. Nevertheless, most of the controllers in the literature do not account for the pressure dynamics of the fluid and treat the system as fully actuated.…”
Section: Introductionmentioning
confidence: 99%